(untitled) (Journal of Medical & Health Sciences Review, 2025)
Non-alcoholic fatty liver disease (NAFLD) is a condition in which surplus fat builds up in liver but this fat buildup is not related to alcohol abuse. Metabolic syndromes such as insulin resistance, dyslipidemia, type II diabetic disease and obesity are also companied with NAFLD. Present study examined the effects of polyherbal powder supplementation on lipid profile, liver enzymes, glycemic status and body mass index. In this randomized, placebo-controlled trail, 30 participants with diagnosed NAFLD were chosen randomly. Participants were randomly subdivided into three groups; control group received only modified diet therapy, group A received modified diet therapy with 5grams of polyherbal powder, group B received 10grams of polyherbal powder. Serum alanine transaminase (ALT), high density lipoproteins (HDL) and low-density lipoproteins (LDL). All the obtained data was statistically analyzed. The polyherbal powder showed significant reduction in all measured parameters. Group B showed significant reductions in Serum ALT as well as lipid profile (p value < 0.05). The results of current study showed that polyherbal powder could be a preferable option for the treatment of NAFLD patients as compared to the hepatoprotective drugs as well as antimetabolic disorders agents. Herbal therapy might be an optimal option if combined with change in lifestyle and proper nutrition and diet intake.